PEMBUATAN DAN VALIDASI BUKU SAKU ELEKTRONIK KEANEKARAGAMAN JENIS TUMBUHAN MANGROVE UNTUK KELAS X SMA/SEDERAJAT - Maryam, Siti; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Teachers"™ limitations in presenting examples of plants including the diversity of species around students"™ environments give rise to low awareness of the existence of plants around them, one of which is mangrove plants. Mangroves must be preserved because they play an important role in the lives of people and other biota. Efforts to preserve mangrove forests can be carried out by disseminating information about the types and importance of mangrove plants through learning media in the form of electronic pocket books. This research aimed to create and validate an electronic pocket book on mangrove species diversity for class X. The research method was descriptive quantitative. Electronic pocket books are made in three stages, namely pre-production, production and post-production. The electronic pocket book was validated in two stages, namely instrument sheet validation and media validation which consisted of 5 aspects, namely format, content, language, effective and practical with 15 criteria. Media validation was carried out by 5 validators using a Likert rating scale. The validation results are explained according to Lawshe (1975). The instrument validation results showed that the instrument was suitable for used, while the media validation results obtained a CVI value of 1.00. This shows that electronic pocket books are categorized as suitable for used as learning media in the class X high school diversity of types sub-material.